Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/app.28700
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silica/polyurethane nanocomposites by UV‐induced polymerization from surfaces of silica

Abstract: UV-curable nanocomposites were prepared by the in situ photopolymerizaton with nanosilica obtained from sol-gel process. The photoinitiator 2-hydroxy-2-methyl-1-phenylpropane-1-one (1173) was anchored onto the surface of the nanosilica with or without methacryloxypropyltrimethoxysilane (MAPS) modification. The photopolymerization kinetics was studied by real-time Fourier transform IR (RTIR), and the microstructure and properties of the nanocomposite were investigated using transmission electron microscopy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…On the other side, cure temperature has also a relevant role in segmented polyurethanes, where a change in its value might cause segregation of the hard segments (HS), altering the dispersion of the nanofiller . Finally, several mixing procedures have been developed for the preparation of thermoset NC, from now on denominated routes. The main difference among those is based on which precursor the filler is dispersed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, cure temperature has also a relevant role in segmented polyurethanes, where a change in its value might cause segregation of the hard segments (HS), altering the dispersion of the nanofiller . Finally, several mixing procedures have been developed for the preparation of thermoset NC, from now on denominated routes. The main difference among those is based on which precursor the filler is dispersed.…”
Section: Introductionmentioning
confidence: 99%
“…Two necessities are required for high light transmittance; one is that the diameter of mSiO 2 nanoparticles should be less than the wavelength of visible light 44. The other is uniformly dispersed nanoparticles in the matrix, which is also confirmed by Ou and Tan in their researches 45, 46. The application of the PHFA/mSiO 2 nanocomposite will be conducted in the following research.…”
Section: Resultsmentioning
confidence: 83%
“…Whilst numerous routes have been established to alter the surface characteristics of SiO 2 and other inorganic materials, only few reports have been focusing on the immobilization of photoinitiators . Nie et al prepared photoactive silica nanoparticles via sol–gel reaction between triethoxysilyl modified 2‐hydroxy‐2‐methyl‐1‐phenylpropane‐1‐one and tetraethyl orthosilicate. FT‐IR experiments revealed that photo‐curing of urethane acrylate monomers in the presence of these modified particles leads to high conversion rates and conversion yields.…”
Section: Introductionmentioning
confidence: 99%